2013
DOI: 10.4102/ijmla.v2i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Context awareness in mobile computing: A review

Abstract: Context awareness is increasingly gaining applicability in interactive ubiquitous mobile computing systems. In order to apply this concept in design of applications for dynamic environments, it is necessary to understand what constitutes context awareness, the classification of context and context-aware development frameworks. The concept of context awareness is discussed, various approaches to context awareness are reviewed, and important aspects of context-aware mobile computing are analysed. Recommendations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 30 publications
1
32
0
1
Order By: Relevance
“…The paper focus on the investigation of several issues concerning research on context-awareness and the extent to which it has been used to handle disaster management. It also focuses on SLR using combined approach and guidelines adapted from Naismith et al (2004), Glass et al (2002) and Musumba and Nyongesa (2013). The authors of the said study utilised four phases method to plan, collate, explore and described the literature-based discoveries.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The paper focus on the investigation of several issues concerning research on context-awareness and the extent to which it has been used to handle disaster management. It also focuses on SLR using combined approach and guidelines adapted from Naismith et al (2004), Glass et al (2002) and Musumba and Nyongesa (2013). The authors of the said study utilised four phases method to plan, collate, explore and described the literature-based discoveries.…”
Section: Methodsmentioning
confidence: 99%
“…Glass et al (2002), Musumba and Nyongesa (2013) and Ramesh et al (2014) 2 have identified context acquisition, sensing, modelling, inference Schmidt, 2013;Champiri et al, 2015) as contending issues in context-awareness services using context interaction. The classification used in this study is employed from similar SLR research articles such as Ampatzoglou and Stamelos (2010), relating the whole idea to the concept of research of interest conducted in this study.…”
Section: Classification Approachmentioning
confidence: 99%
“…While it might be trivial to represent raw contextual data, it is not easy to model context of high level of abstraction. Perttunen et al (2009), Kofod-petersen & Mikalsen (2005 and Moldovan & Clark (2005) emphasised the importance of context modelling for its subsequent mapping into a higher level and reasoning. While ontologies provide a power approach, fuzzy logic or non-classical logical construct, such as modal, temporal and many valued logic are anticipated to offer a power solution for context representation.…”
Section: Fundamentals Of Artificial Intelligencementioning
confidence: 99%
“…As envisioned by Weiser (1991), and elaborated by Abowd (2016b) computers have to foresee human actions and act proactively to offer expected assistance (Abowd, 2012;Schilit et al, 1994). To do so, any information characterizing a situation of the interaction between users, applications, and the environment can be regarded as context (Musumba & Nyongesa, 2013). An understanding of context will help designers and system architects to use it effectively (Dey, 2001), and lead to a new component of ubiquitous computing called context-aware computing.…”
Section: Introductionmentioning
confidence: 99%
“…An entity could be a person, a place or an object while information refers to any particular element or detailed piece of data that allows for the description of any condition or state of the participating entities. Context-awareness is a mobile computing paradigm in which applications can discover and take advantage of contextual information such as user location, time of day, neighbouring users and devices, and user activity [19]. In [20], the authors identified location, identity, time, and activity as primary context types for characterizing the situation of a particular entity.…”
Section: Context and Context-awareness Modelsmentioning
confidence: 99%